Drug survival of anakinra and canakinumab in monogenic autoinflammatory diseases: observational study from the International AIDA Registry. (7th May 2021) - Sota, Jurgen; Rigante, Donato; Cimaz, Rolando; Cattalini, Marco; Frassi, Micol; Manna, Raffaele; Sicignano, Ludovico Luca; Verrecchia, Elena; Aragona, Emma; Maggio, Maria Cristina; Lopalco, Giuseppe; Emmi, Giacomo; et al.
Abstract: Objectives: To investigate survival of IL-1 inhibitors in monogenic autoinflammatory disorders (mAID) through drug retention rate (DRR) and identify potential predictive factors of drug survival from a real-life perspective. Patients and methods: Multicentre retrospective study analysing patients affected by the most common mAID treated with anakinra or canakinumab. Survival curves were analysed with the Kaplan-Meier method. Statistical analysis included a Cox-proportional hazard model to detect factors responsible for drug discontinuation. Results: Seventy-eight patients for a total of 102 treatment regimens were enrolled. The mean treatment duration was 29.59 months. The estimated DRR of IL-1 inhibitors at 12, 24 and 48 months of follow-up was 75.8%, 69.7% and 51.1%, respectively. Patients experiencing an adverse event had a significantly lower DRR ( P= 0.019). In contrast, no significant differences were observed between biologic-naïve patients and those previously treated with biologic drugs ( P= 0.985). Patients carrying high-penetrance mutations exhibited a significantly higher DRR compared with those with low-penetrance variants ( P= 0.015). Adverse events were the only variable associated with a higher hazard of treatment withdrawal [hazard ratio (HR) 2.573 (CI: 1.223, 5.411), P= 0.013] on regression analysis. A significant glucorticoid-sparing effect was observed ( P< 0.0001). Conclusions: IL-1 inhibitors display an excellent long-term effectiveness in terms of DRR, and their survival is not influenced by the biologic line of treatment. They display a favourable safety profile, which deserves, however, a close monitoring given its impact on treatment continuation. Special attention should be paid to molecular diagnosis and mutation penetrance, as patients carrying low-penetrance variants are more likely to interrupt treatment.